CODE-MIXING ANALYSIS IN BILINGUAL CONVERSATIONS ON PODCAST MEDIA - Ani Deswita Chaniago; Laila Hasyim; Mariana M; Syafrizaldi S; Linda Hernike Napitupulu (Journal Analytica Islamica, 2025)
This study aims to analyze the forms and distribution of code-mixing in bilingual conversations between Cinta Laura and Maudy Ayunda on the Puella podcast, using Muysken's (2000) theoretical framework. Employing a descriptive qualitative approach, this research identifies three main types of code-mixing Insertion, Alternation, and Congruent Lexicalization to reveal their linguistic and social functions. The data consist of 77 lines of conversation extracted from the YouTube Puella channel, which were classified and analyzed based on the context of their use. The results indicate that Alternation is the most dominant type, accounting for 50.65% of occurrences, followed by single-language use (Indonesian 18.18% and English 16.88%), Congruent Lexicalization (6.49%), and Insertion (3.90%). The predominance of Alternation demonstrates the speakers' flexibility in switching between languages and reflects their strong bilingual identity. Functionally, code-mixing serves as an effective communication strategy to enhance self-expression, establish rapport with bilingual audiences, and represent the socio-cultural dynamics of the young generation in the global era. This study provides an empirical contribution to sociolinguistic research by emphasizing code-mixing as both a linguistic and social phenomenon enriching communication practices in digital media.